2021
DOI: 10.1017/jfm.2021.762
|View full text |Cite
|
Sign up to set email alerts
|

Structured input–output analysis of transitional wall-bounded flows

Abstract: Input–output analysis of transitional channel flows has proven to be a valuable analytical tool for identifying important flow structures and energetic motions. The traditional approach abstracts the nonlinear terms as forcing that is unstructured, in the sense that this forcing is not directly tied to the underlying nonlinearity in the dynamics. This paper instead employs a structured-singular-value-based approach that preserves certain input–output properties of the nonlinear forcing function in an effort to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 87 publications
(139 reference statements)
3
29
0
Order By: Relevance
“…In this paper, we have extended the structured input-output analysis (SIOA) originally developed for unstratified wall-bounded shear flows (Liu & Gayme 2021) to stratified plane Couette flow (PCF). We first apply SIOA to characterize highly amplified flow structures in the intermittent regimes of stratified PCF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, we have extended the structured input-output analysis (SIOA) originally developed for unstratified wall-bounded shear flows (Liu & Gayme 2021) to stratified plane Couette flow (PCF). We first apply SIOA to characterize highly amplified flow structures in the intermittent regimes of stratified PCF.…”
Section: Discussionmentioning
confidence: 99%
“…We need to define the spatio-temporal frequency response H S ∇ (y; k x , k z , ω) of stratified PCF that will form the basis of the structured input-output response. We use the superscript S to distinguish this operator from its counterpart for unstratified wallbounded shear flow (Liu & Gayme 2021). We employ the standard transformation to express the velocity field dynamics in (2.1) in terms of a formulation using the wall-normal velocity v and the wall-normal vorticity ω y := ∂ z u − ∂ x w (Schmid & Henningson 2012).…”
Section: Structured Input-output Responsementioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we extend the structured input-output analysis (SIOA) originally developed for unstratified PCF (Liu & Gayme 2021) to stratified PCF. Prior application of the SIOA approach to unstratified transitional wall-bounded shear flows (Liu & Gayme 2021) demonstrated that including the componentwise structure of the nonlinearity uncovers a wider range of known key flow features identified through nonlinear analysis, experiments and DNS, but not captured through traditional (unstructured) input-output approaches.…”
Section: Introductionmentioning
confidence: 99%